An investigation on Alzheimer’s disease with obstructive sleep apnea: alterations of cognitive function, roles of cyclin-dependent kinase 5 and changes of brain structure - Luo, Dongmei; Lian, Tenghong; Wei, Ning; Guo, Peng; He, Mingyue; Zhang, Yanan; Huang, Yue; Liu, Gaifen; Li, Jinghui; Li, Jing; Qi, Jing; Guan, Huiying; et al. (Frontiers in Aging Neuroscience, 2025)
AimsTo investigate alterations of cognitive function, roles of cyclin-dependent kinase 5 (CDK5) and changes of brain structure in Alzheimer’s disease (AD) with obstructive sleep apnea (OSA).MethodsTotal 94 AD with OSA (AD-OSA) patients were divided into 49 cases of AD with mild OSA (AD-OSA-M) and 45 cases of AD with moderate and severe OSA (AD-OSA-MS). Demographic characteristics, cognitive function, the levels of AD neuropathological proteins, CDK5 and synaptic proteins in cerebrospinal fluid (CSF), and brain volume by magnetic resonance imaging were compared between the two groups. The correlations among OSA and the above variables were analyzed.ResultsCompared with AD-OSA-M group, AD-OSA-MS group had a higher body mass index, lower scores of AVLT N7 and SCWT-C, longer SCWT-C time, higher levels of phosphorylated tau (P-tau) 396 and synaptophysin, lower CDK5 level and smaller volumes of brain gray and white matters in parts of frontal, parietal, temporal and occipital lobes. In AD-OSA patients, the decreased CDK5 level was correlated with the elevated levels of P-tau 396 and synaptophysin in CSF. In AD-OSA-MS group, reductions of gray matter and white matter volumes associated with OSA exacerbation was correlated with memory and executive function impairments. The p-values of above results were <0.05.ConclusionIn AD-OSA, OSA exacerbation is associated with memory impairment and executive dysfunction, P-tau 396 elevation and CDK5 decline in CSF, synaptic disruption, and brain atrophy. Additionally, CDK5 may represent a potential therapeutic target for the individuals with comorbid AD and OSA.